Automation of human semen analysis using a novel artificial intelligence optical microscopic technology. (4th October 2019) - Agarwal, Ashok; Henkel, Ralf; Huang, Chun‐Chia; Lee, Maw‐Sheng
Abstract: Current semen analysis still commonly depends on a manual microscopy method in clinical laboratories worldwide. However, some of the major disadvantages of this technique are that it is labour‐intensive, subjective, laboratory‐based and time‐consuming. Although computer‐assisted semen analysers (CASAs) have enabled partial automation of routine semen analysis, they lack wider acceptance due to their complicated operation. Therefore, the development of an accessible, rapid and standardised method for semen analysis is urgently needed. Here, we describe the development and clinical testing of a novel, automated, artificial intelligence optical microscopic (AIOM)‐based technology, LensHooke™ X1 PRO (X1 PRO), designed for the quantitative measurement of sperm concentration, motility and seminal pH. We observed high degree of correlation in the results of concentration, progressive motility and progressively motile sperm concentration between the X1 PRO semen analyser and manual method using 135 clinical semen samples. In addition, the seminal pH results obtained by X1 PRO and manual methods were comparable ( p  = .12). In summary, our results showed that new X1 PRO semen analyser is a reliable diagnostic tool for routine semen analysis providing clinically acceptable results based on World Health Organization (WHO) 5th Edition guidelines.